Quantities of Falling dust in the province of Babylon from 2009 to 2012 - Mahammed E. Jabbar Al-Defiery; Abbas Khudair Abbas; Mouayed Abed Alwahed (Journal of Madenat Alelem University College, 2017)
Serious problems caused by the dust pollution from desertification and some human activities that have a negative impact on human health. It is required to study and determine of falling dust for developing effective treatments. It was measured amounts of falling dust every month on three areas within the center of the province of Babylon (residential, industrial and agricultural areas) and three districts of the province of Babylon (Hashemite، Mahawil and Musayib) during the years 2009-2012. The results showed that the highest amount of dust were observed in center of Babylon province during May of year 2012, April of two years (2011 and 2010) and June of year 2009 with rates 134.30، 166.67، 92.53،122.82 g / m2 / month respectively. While the industrial areas showed the highest ratio of falling dust concentrations through the research years. The Hashemite district on year 2009 and the Mahawil district on years (2011 and 2012) as recorded highest average of falling dust annual concentrations, also the May of 2012 was recorded highest rate of falling dust concentration (148.13 g / m2 / month) on the districts of Babylon province within years of research. In 2012, it was found higher average of falling dust concentrations than the past three years. Therefore, they recommend the following plans of the appropriate and effective solutions that capable to guarantee for treatment achievement of the causes leading to increase levels of dust in the air of Babylon province.